Ab initio random structure searching of organic molecular solids: assessment and validation against experimental data. Issue 38 (25th September 2017) - Zilka, Miri; Dudenko, Dmytro V.; Hughes, Colan E.; Williams, P. Andrew; Sturniolo, Simone; Franks, W. Trent; Pickard, Chris J.; Yates, Jonathan R.; Harris, Kenneth D. M.; Brown, Steven P.
Abstract : The AIRSS method generates crystal structures for m -aminobenzoic acid; comparison is made to experimental powder X-ray diffraction and MAS NMR. Abstract : This paper explores the capability of using the DFT-D ab initio random structure searching (AIRSS) method to generate crystal structures of organic molecular materials, focusing on a system ( m -aminobenzoic acid; m -ABA) that is known from experimental studies to exhibit abundant polymorphism. Within the structural constraints selected for the AIRSS calculations (specifically, centrosymmetric structures with Z = 4 for zwitterionic m -ABA molecules), the method is shown to successfully generate the two known polymorphs of m -ABA (form III and form IV) that have these structural features. We highlight various issues that are encountered in comparing crystal structures generated by AIRSS to experimental powder X-ray diffraction (XRD) data and solid-state magic-angle spinning (MAS) NMR data, demonstrating successful fitting for some of the lowest energy structures from the AIRSS calculations against experimental low-temperature powder XRD data for known polymorphs of m -ABA, and showing that comparison of computed and experimental solid-state NMR parameters allows different hydrogen-bonding motifs to be discriminated.